IOT : development of a home automation system 1 - Loh, Han Yang (Nanyang Technological University, 2021)
Home automation is an area widely explored due to technological advancement and increasing popularity. From security to monitoring purposes, home automation covers a wide range and provides solution to users away from home. As home automation encompasses a broad range of tools, it can include security monitoring as well as long range control of home devices through IOT. By using existing infrastructure, this project seeks to make home automation simple to implement for the mass market. Providing home automation with IOT devices for increased adoption is the idea behind this project. The project focuses on building an infrastructure capable for mass market adoption.